Role of Mouse Organic Anion Transporter 3 (mOat3) as a Basolateral Prostaglandin E2 Transport Pathway - Sirinun Nilwarangkoon; Naohiko Anzai; Katsuko Shiraya; Erkang Yu; Rafiqul Islam; Seok Ho Cha; Maristela Lika Onozato; Daisaku Miura; Promsuk Jutabha; Akihiro Tojo; Yoshikatsu Kanai; Hitoshi Endou (Elsevier, 2007)
Renal organic anion transporters play an important role in the handling of a number of endogenous and exogenous anionic substances in the kidney. In this study, we investigated prostaglandin E2 (PGE2) transport properties and intrarenal localization of mouse organic anion transporter 3 (mOat3). When expressed in Xenopus oocytes, mOat3 mediated the time- and concentration-dependent transport of PGE2 (Km: 1.48 µM). PGE2 transport mediated by mOat3 was trans-stimulated by intracellular glutarate injected into the oocytes. PGE2 efflux via mOat3 was also trans-stimulated by extracellular glutarate. Thus, mOat3 was shown to mediate the bidirectional transport of PGE2, partly coupled to the dicarboxylate exchange mechanism. Immunohistochemical study revealed that mOat3 protein was localized at the basolateral membrane of renal proximal and distal tubules. Furthermore, diffuse expression of mOat3, including expression in the basolateral membrane in macula densa (MD) cells, was observed. These results indicate that mOat3 plays an important role as a basolateral transport pathway of PGE2 in the distal nephron including MD cells that may constitute one of the indispensable steps for renin release and regulation of the tubuloglomerular feedback mechanism. Keywords:: organic anion transporter, OAT, prostaglandin E2, glutarate, macula densa